ANALYSIS OF THE USE OF THE WORDWALL APPLICATION IN LEARNING ENGLISH USING CHROMEBOOK FOR VOCABULARY - KHASYI, RAMDANI ASTIN ABIYU (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This study aims to explore the subjective experiences, perceptions, and challenges faced by English teachers and students in implementing the WordWall application in their classroom environment, especially when used together with Chromebooks to learn vocabulary. The research method used is qualitative by collecting data through interviews, questionnaires and observation. The results of interviews with teachers showed that WordWall was assessed positively in increasing student engagement and vocabulary understanding, even though several technical challenges such as slow internet connections were encountered. Student questionnaires also yielded positive responses, with the majority of students feeling more engaged and their vocabulary understanding improved after using WordWall. Observation results indicate that WordWall in combination with Chromebooks is effective in creating an interactive learning environment that facilitates student engagement. In conclusion, using WordWall with Chromebooks can be an effective tool in enhancing English language learning in the classroom, by offering students an engaging and interactive learning experience.